Chromatographic profiling of Sanitizers for forensic investigation - Sipayang, Patsy Petrus J (2020)
Hand hygiene had been an important requirement to maintain good health. Nowadays, sanitizer had been used for hand hygiene routine besides the traditional method using soap and water. As more sanitizers were introduced into the market, there is a need to know whether the available sanitizers are meeting the right standard. Therefore, this study was aimed to discriminate the various sanitizers collected from local markets using chromatographic technique. In this study, hand sanitizers samples were extracted by Solid-Phase Microextraction (SPME) method and subsequently analysed by Gas Chromatography-Flame Ionisation Detector (GC-FID). Then, Principal Component Analysis (PCA) chromatographic and Hierarchical Cluster Analysis (HCA) were used to generate the data to observe any clustering or discrimination among the samples. From the chromatographic profiles, all samples showed the presence of alcohol compounds as the main ingredients. Based on the PCA score plot, 3D scatter plot and dendrogram, two main clusters were observed and there were four samples that did not include in both the clusters. These four hand sanitizer samples could have carried different chromatographic information from other samples tested in this study. In conclusion, this study had successfully generated the hand sanitizer profiles from different brands and differentiated certain samples based on their respective chromatographic profiles.